2012
DOI: 10.1007/s00299-012-1228-x
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase is involved in nitric oxide- and auxin-induced lateral root formation in rice

Abstract: Lateral root (LR) development performs the essential tasks of providing water, nutrients, and physical support to plants. Therefore, understanding the regulation of LR development is of agronomic importance. In this study, we examined the effect of nitric oxide (NO), auxin, and hemin (Hm) on LR formation in rice. Treatment with Hm [a highly effective heme oxygenase (HO) inducer], sodium nitroprusside (SNP, an NO donor), or indole-3-butyric acid (IBA, a naturally occurring auxin) induced LR formation and HO act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 31 publications
(50 reference statements)
0
22
1
Order By: Relevance
“…8,9 Our recent results revealed that HO is involved in nitric oxide and auxin-induced LR formation in rice. 10 We also provided indirect evidence to show that CO increases HO activity in rice. 10 However, it is not known whether BV, another product of HO catalyzed reaction, promotes LR formation in rice.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…8,9 Our recent results revealed that HO is involved in nitric oxide and auxin-induced LR formation in rice. 10 We also provided indirect evidence to show that CO increases HO activity in rice. 10 However, it is not known whether BV, another product of HO catalyzed reaction, promotes LR formation in rice.…”
mentioning
confidence: 64%
“…10 We also provided indirect evidence to show that CO increases HO activity in rice. 10 However, it is not known whether BV, another product of HO catalyzed reaction, promotes LR formation in rice.…”
mentioning
confidence: 64%
“…The HEME OXYGENASE 1 ( HOX1 ) gene controls the formation of lateral roots via the production of carbon monoxide. HOX1 is regulated by auxin and stress related signals, such as jasmonate and nitric oxide (Chen et al [ 2012 ]; Hsu et al [ 2012 ]), which suggests that this pathway can contribute to the modulation of root architecture in response to stress.…”
Section: Reviewmentioning
confidence: 99%
“…14 In another recent report, we demonstrated that SNP and IBA could induce OsHO1 mRNA expression. 15 LR formation and HO activity induced by SNP and IBA was reduced by cPTIO and Zn protoporphyrin (ZnPPIX, the specific inhibitor of HO). 15 It seems that HO is required for auxin-and NO-induced LR formation in rice (Fig.…”
Section: Role Of Rice Heme Oxygenase In Lateral Root Formationmentioning
confidence: 99%